RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND FAT PERCENTAGE WITH CARDIOVASCULAR ENDURANCE IN EXTRACURRICULAR FUTSAL STUDENTS AT SMKN 2 KUNINGAN FROM A GENDER PERSPECTIVE - Zani, Syabilla; Reshandi Nugraha (SAINS INDONESIANA, 2025)
This study aims to determine the relationship between nutritional status and body fat percentage with cardiovascular endurance in futsal extracurricular students. The study used a quantitative descriptive method with a correlational design involving 50 samples using BMI measurement tools for nutritional status, Karada Scan for body fatpercenta ge, and beep test for cardiovascular endurance. The overall analysis of the samples revealed that nutritional status did no  have a significant relationship with endurance, with a correlation coefficient of -0.064 and a significance level of 0.658. However, body fat percentage showed a strong and significant negative correlation with endurance, with a correlation coefficient of -0.714 and a significance level of 0.000. The results from the male sample showed a significant negative correlation, while the female sample did not show a significant correlation. The overall correlation values indicate that as body fat percentage increases, cardiovascular endurance tendsto decrease. However, regarding nutritional status, it has not been proven that anunfavorable nutritional status correlates with a decrease in cardiovascular endurance.